Handbook of interpersonal communication - Knapp, Mark L. (Sage Publ., 1994)
Nine years after the First Edition, key scholars redefine the field of interpersonal communication. New chapters, which represent areas of contemporary concern, focus on culture and meaning, supportive communication and health care.